2010
DOI: 10.2214/ajr.09.3393
|View full text |Cite
|
Sign up to set email alerts
|

MR Arthrography of the Second and Third Metatarsophalangeal Joints for the Detection of Tears of the Plantar Plate and Joint Capsule

Abstract: Most metatarsophalangeal joint capsular tears occur at the distal lateral border of the plantar plate, often with injury of the adjacent interosseous tendon. Plantar plate tears are less common. MR arthrography of the metatarsophalangeal joint delineates capsular tears and associated abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 8 publications
0
24
0
2
Order By: Relevance
“…MR arthrography confirmed deficiencies in 10 plantar plates, extravasation of contrast agent was seen in the surrounding soft tissue of 6, confirming a tear in the capsule, and extravasation of contrast agent was seen in the flexor tendon of only 4, confirming a true plantar plate tear 11 . Two plantar plates showed no extravasation of contrast agent on arthrography (contrast agent was not successfully injected into 1 joint); both demonstrated high signal at the insertion on standard MR.…”
Section: Rheumatologymentioning
confidence: 82%
See 3 more Smart Citations
“…MR arthrography confirmed deficiencies in 10 plantar plates, extravasation of contrast agent was seen in the surrounding soft tissue of 6, confirming a tear in the capsule, and extravasation of contrast agent was seen in the flexor tendon of only 4, confirming a true plantar plate tear 11 . Two plantar plates showed no extravasation of contrast agent on arthrography (contrast agent was not successfully injected into 1 joint); both demonstrated high signal at the insertion on standard MR.…”
Section: Rheumatologymentioning
confidence: 82%
“…Previous studies in cadaveric specimens and subjects without RA have compared standard MR imaging with MR arthrography in diagnosing soft tissue pathology at the lesser MTP joints 6,10,11 . These studies have suggested that MR arthrography improves visualization of the structures and delineates capsule tears from plantar plate tears.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zur Darstellung von Verletzungen der plantaren Platte wurden Ultraschall, konventionelle Arthrographie, MRT und MR-Arthrographie eingesetzt, wobei der Ultraschall unter Dorsalflexion der betroffenen Zehe als aussagekräftiges und gleichzeitig einfaches Verfahren angesehen wird [2,8,9].…”
Section: Cmeunclassified